Purificação, caracterização físico-química e estrutural de uma lectina da esponja marinha Cinachyrella alloclada - Marques, Juliana Sampaio Nogueira (2021)
Sponges are animals belonging to the Porifera phylum, one of the oldest and most morphologically simple of the existing metazoan phyla. Sponges belonging to the genus Cinachyrella are often called “golf ball sponges” and “moon sponges” because of their spherical shape and circular depressions (porocalices) that commonly appear on their surface. Marine sponges have drawn attention for having a range of bioactive chemical components and molecules with promising biotechnological applications and, among these molecules, are the lectins, which are proteins or glycoproteins that have specific and reversible binding to carbohydrates and that have several biological activities already described, such as cytotoxic, mitogenic, anti-cancer, anti-HIV and anti-biofilm effects. A lectin from Cinachyrella alloclada (CalL) was purified by a combination of precipitation with 70% ammonium sulfate, ion exchange chromatography on a DEAE-Sephacel column and size exclusion on a Sephacryl S 300 HR column. The CalL lectin preferentially agglutinated type O trypsinized erythrocytes and its hemagglutinating activity was inhibited by galactosides and mucins. The lectin activity was maximum at pH 7.0, showed thermostability up to 50 °C and did not depend on divalent cations. The molecular mass of the monomer was estimated at 16 kDa. The amino acid sequences of the identified peptides make up about 73% of the primary structure of the lectin, and are similar to other marine sponge galectins. Thus, the CalL lectin can be used in future studies to assess its potential application as a biotechnological tool.